2007
DOI: 10.3174/ajnr.a0621
|View full text |Cite
|
Sign up to set email alerts
|

The Venous Distension Sign: A Diagnostic Sign of Intracranial Hypotension at MR Imaging of the Brain

Abstract: BACKGROUND AND PURPOSE:Patients with intracranial hypotension (IH) demonstrate intracranial venous enlargement with a characteristic change in contour of the transverse sinus seen on routine T1-weighted sagittal imaging. In IH, the inferior margin of the midportion of the dominant transverse sinus acquires a distended convex appearance; we have termed this the venous distension sign (VDS). This is distinct from the normal appearance of this segment, which usually has a slightly concave or straight lower margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 23 publications
4
79
0
1
Order By: Relevance
“…All patients had orthostatic headache, and nausea was seen in 2, hearing loss in 2, tinnitus in 1, dizziness in 1, and stiff neck in 1 patient. MR images obtained from all pretreatment patients demonstrated all of the following findings described in previous reports [1][2][3][4][5][6][7][8][9] : enlargement of the venous sinuses, enlargement of the pituitary gland, thickening and enhancement of the dura mater, and downward displacement of the brain (sagging brain) (Fig 1A, -B).…”
Section: Patientssupporting
confidence: 74%
See 3 more Smart Citations
“…All patients had orthostatic headache, and nausea was seen in 2, hearing loss in 2, tinnitus in 1, dizziness in 1, and stiff neck in 1 patient. MR images obtained from all pretreatment patients demonstrated all of the following findings described in previous reports [1][2][3][4][5][6][7][8][9] : enlargement of the venous sinuses, enlargement of the pituitary gland, thickening and enhancement of the dura mater, and downward displacement of the brain (sagging brain) (Fig 1A, -B).…”
Section: Patientssupporting
confidence: 74%
“…10 However, within the brain, the blood-brain barrier restricts the extracellular fluid expansion generating interstitial edema, primarily resulting in an increase in the volume of the vessels and meninges. 9 On the other hand, on reviewing MR images of patients with SIH, we visually observed on FLAIR images that the signal intensity of the subcortical white matter was decreased, with the border between the cortex and subcortical white matter being more readily distinguishable than in healthy control Fig 3. A, A pretreatment FLAIR image obtained from case 1 when the symptoms were intense shows that the signal intensity of the subcortical white matter is apparently lower than that of the cortex, with the border between them being readily distinguishable (arrows).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Once considered a rare entity, recent understanding of the pathophysiology and the radiologic identification of this syndrome resulted in the increase in the number of recognized cases, and recent reports showed that the incidence of this syndrome may be indeed much higher than presumed [1,5,9,14]. The estimated incidence of SIH is 1:50,000, with a female predominance [6].…”
Section: Discussionmentioning
confidence: 99%